KEMAMPUAN ANAK PENDERITA AUTIS DALAM MEMAHAMI TINDAK TUTUR DIREKTIF: TINJAUAN PRAGMATIK KLINIS - Nurul Fitrah Yani (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2017)
Abstract. The Ability Of Children With Autism  In Comprehending  The Directive Speech Acts: Pragmatik Review Of Clinical. The aim of the study were to (1) describe the ability of autistic children to komprehend directive speech, and (2) describe the ability of autistic children to produce directive speech. This research was a case study with qualitative descriptive anlysis. Located at Bunda Autistic School at Makassar. The data resource were three children and supervisory teacher as a key informer. The research was conducted for two months from February to April 2014. The result of reseach indicated that (1) almost all forms of nonverbal responses performed, especially by children with autism, were characterized by moderate and severe (AAS and AAB)autistics. Verbal response can only be performed by autistics with mild characreristic, AAS. (2) the AAR autistic children had good ability to explain half of the existing category in performing direct speech, AAS had good enough ability and was able to explain some of existing category, but not more then AAR, the ability of AAB in explaining TTD was low and limited. From the existing category, the AAB was only able to produce of TTD in one case only.